The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/pssc.200779441
|View full text |Cite
|
Sign up to set email alerts
|

Influence of treatment conditions on chalcopyrite films deposited at atmospheric pressure

Abstract: Spin‐coating technique was used to deposit precursor layers for chalcopyrite films of the series CuInX2 and Cu(In,Ga)X2 where X = S or Se or (S,Se). The influence of different parameters of the process, such as solution composition, air pre‐treatment and chalcogenation treatment is discussed with respect to film applicability in photovoltaic devices. Layer morphology, stochiometry and crystalline structure varied widely with the different compositions and treatments. Highly oriented CuInSe2 and Cu(In,Ga)Se2 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…However, as shown in the cross-section micrograph, there were no obvious crystalline grains although our films had larger grain than the film prepared by a similar method [24]. Todorov et al [25] found that the carbon purity prohibited crystal growth in the CIGS film during thermal treatment. It is well known that the efficiency of polycrystalline solar cells increases with increasing grain size in the absorber layer.…”
Section: Selenized Layermentioning
confidence: 86%
“…However, as shown in the cross-section micrograph, there were no obvious crystalline grains although our films had larger grain than the film prepared by a similar method [24]. Todorov et al [25] found that the carbon purity prohibited crystal growth in the CIGS film during thermal treatment. It is well known that the efficiency of polycrystalline solar cells increases with increasing grain size in the absorber layer.…”
Section: Selenized Layermentioning
confidence: 86%
“…While oxide coatings are often treated in air, in order to eliminate carbon contamination, [77][78][79] air-sensitive samples are handled in inert atmosphere. [80][81][82] The final high temperature heat treatment (350-600°C) always requires controlled atmosphere, often with the addition of chalcogen vapor or hydrogen chalcogenide.…”
Section: Direct Liquid Coating Methodsmentioning
confidence: 99%
“…Gallium oxides are exceptionally difficult to reduce. Ga-incor- Oxides allow air anneal to burn out residual difficulty to remove oxygen completely from final suspension, 13.6 % [91] carbon from additives film Metals similarity to standard sequential vachigh tendency to alloy and aggregate, possible phase suspension, 10 % [90] uum processes segregation Salts off-the-shelf chemicals and multiple op-difficulty to form high quality layers due to crystalli-solution, 6.7 % [87] tions for choice of salt zation of precursor layer and impurities from salt Metalallow the formation of metallic laycarbon and/or oxygen contamination in final film; solution, 9 % [88] organics ers [88] or reactive amorphous oxides [78] low critical thickness per layer poration and desirable grading was achieved through subsequent in-diffusion of a gallium compound. [94] Solution-based (as opposed to nanoparticle or suspension based) approaches leading to in-situ formation of oxide precursor films have also been developed.…”
Section: Methods Employing Oxide Precursor Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works we described a soft-chemistry route for in situ synthesis of compact nanoparticulate Cu(In,Ga)O x films which were successfully converted into CuInS 2 , CuInSe 2 and Cu(In,Ga)Se 2 [10][11][12].…”
Section: Introductionmentioning
confidence: 99%